HUBUNGAN EFIKASI DIRI DAN DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUP DR. SITANALA TANGERANG - Anggi Mulyana Rahayu (2023)
Chronic kidney failure patients undergoing hemodialysis therapy will undergo therapy continuously and is a factor that can cause a decrease in quality of life. Quality of life will improve if individuals are able to accept the disease they are experiencing. Self-efficacy and good family support can increase confidence for treatment. The purpose of this study was to analyze the relationship between self-efficacy and family support on the quality of life of chronic kidney failure patients undergoing hemodialysis at RSUP Dr. Sitanala Tangerang. The research method uses a quantitative design with cross sectional method and is analyzed by the chi-square correlation test. Sampling method with side purposive from 76 population to 70 respondents. The instruments in this study used Chronic Kidney Disease Self Efficacy, Nursalam Family Support and Kidney Disease Quality of Life (KDQOL-36). The results showed that there was a relationship between self-efficacy and quality of life, p-value 0,020 (<0,05) and OR = 3,927; between family support and quality of life p-value 0,002 (<0,05) and OR = 6,458. so, it can be concluded that there is a significant relationship between self-efficacy and quality of life and family support with quality of life. Researchers hope that good self-efficacy and family support can influence the quality of life so that patients can continue to improve and maintain their quality of life.